Contemporary issues in protein requirements and consumption for resistance trained athletes - Wilson, J.; Wilson, G. J. (Journal of the International Society of Sports Nutrition, 2006)
In recent years an explosion of research papers concerning protein consumption has been published. The need to consolidate this information has become critical from both practical and future research standpoints. For this reason, the following paper presents an in depth analysis of contemporary issues in protein requirements and consumption for resistance trained athletes. Specifically, the paper covers: 1.) protein requirements for resistance trained athletes; 2.) the effect of the digestion rate of protein on muscular protein balance; 3.) the optimal timing of protein intake relative to exercise; 4.) the optimal pattern of protein ingestion, relative to how an individual should consume their protein throughout a 24 hour period, and what sources are utilized during this time frame; 5.) protein composition and its interaction with measures of protein balance and strength performance; 6.) the combination of protein and carbohydrates on plasma insulin levels and protein balance; 7.) the efficacy of protein supplements and whole food protein sources. Our goal is to provide the reader with practical information in optimizing protein intake as well as for provision of sound advice to their clients. Finally, special care was taken to provide future research implications.